PERIODE HIJRAH DAN MADINAH - Baihaqi Hirza; M. Yaffi Rabbani; Ucok Kurnia Meliala Hasibuan (Jurnal Intelek Insan Cendikia, 2025)
The event of Hijrah and the Medina period of the Prophet Muhammad SAW represent an important moment in Islamic history that marks the transformation of Islamic preaching from a struggle filled with challenges in Mecca to the establishment of the first Islamic state in Medina. Hijrah was not just a physical relocation, but it also paved the way for the Prophet Muhammad SAW to build a social, political, and religious order based on the principles of Islam. During the Medina period, the Prophet SAW led the formation of an inclusive society through the Medina Charter, which regulated the relationships among groups based on the principles of justice and unity. This period also included various wars that tested the resilience of the Muslim community, as well as the implementation of Islamic law that is fundamental to the revelations of Allah and the Sunnah of the Prophet. The Medina period became a model of an Islamic state that emphasizes peace, justice, and the welfare of the community.